ANÁLISE DO COURO CABELUDO DE MULHERES COM AIDS SUBMETIDAS À AUTÓPSIA: aspectos epiteliais, foliculares e imunológicos - Faria, Humberto Aparecido (2011)
Introduction: Several diseases of skin and scalp (S) occur with greater clinicalseverity in individuals infected with HIV. With the emergence and effectiveness of HAART, there was a decrease in the incidence of the processes associated withimmunodeficiency, and the emergence of apparently less serious problems, such as onychodystrophy, seborrheic dermatitis and alopecia. There is an increasing number of AIDS cases in females, and frequent complaints of these women in relation to changes of the S. The hypothesis of this study is that HIV causes morphological changes in the S, changing its local immunity Objectives: To evaluate the thickness of the epidermis, the number of epithelial cell layers, the diameter of the epithelial cells, the amount of collagen fibers (CF) and elastic fibers (EF), hair follicles (HF), Langerhans cells (LC ) and the presence of general pathological processes (GPP) in the S of autopsied women with AIDS. Materials and Methods: Were evaluated 28 S fragments of women aged between 18 and 46 years. The patients were divided into two groups: those with AIDS (N = 14) and without AIDS (N = 14). Histochemical analysis were performed: hematoxylin and eosin for epidermal thickness, number of epithelial cell layers, the diameter of the epithelial cells, HF count and evaluation of GPP; picrosirius for quantification of CF; Verhoeff for EF; and immunohistochemistry with the antibody anti-S100 for quantification of LC. Morphometrical analysis was performed using the softwares KS300 (Kontrol Zeiss) and Leica Qwin. Results: The cases with AIDS presented reduction of the total HF number and increased percentage of telogen HF. There was reduction of all other morphometric parameters evaluated at the S of women with AIDS, with no significant values inrelation to the number of total LC and percentage of total CF. Conclusions: This study demonstrates that there is a reduction of the integrity of the S of women with AIDS, providing parameters for a better clinical and morphological diagnosis of these patients.